Factors Causing Domestic Violence (KDRT) from a Legal and Religious Aspect - Warsono, Warsono (West Science Social and Humanities Studies, 2025)
This study aims to analyze the causes of domestic violence (DV) from a legal and religious perspective. This type of research is field research with a descriptive qualitative approach. Sources were obtained directly from perpetrators of domestic violence victims, police, and religious leaders in Tanjung Raya District, Mesuji Regency. Data collection used interviews, observation, and documentation. Data analysis used data reduction techniques, data presentation, and conclusion drawing. The results of this study are husbands' errors in understanding the concept of marriage, a lack of openness in the family, husbands' dissatisfaction with their wives' incompetence, economic conditions, the perpetrators' character who tends to be quick to anger, lack of supervision, and the responses of local residents and close families in responding to acts of violence.